2017
DOI: 10.1186/s13019-017-0588-2
|View full text |Cite
|
Sign up to set email alerts
|

Redo coronary bypass grafting for congenital left main coronary atresia: a case report

Abstract: BackgroundCongenital left main coronary atresia is an extremely rare coronary anomaly. Long-term surgical outcomes and the optimal management strategies for recurrence of ischemia remain uncertain. Herein, we present a case involving successful redo coronary artery bypass grafting for unstable angina 27 years after the initial coronary artery bypass grafting for congenital left main coronary atresia.Case presentationA 33-year-old woman was referred to our department with unstable angina. At the age of 6, she h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Catastrophic situations like sudden cardiac arrest, low cardiac output, and cardiomyopathy, as seen in our case, can also be the first symptoms of infants with LMCAA. [5,6] Since these symptoms are not specific to LMCAA, the clinical diagnosis might be neglected. Thus, other coronary anomalies should be excluded to reach a correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Catastrophic situations like sudden cardiac arrest, low cardiac output, and cardiomyopathy, as seen in our case, can also be the first symptoms of infants with LMCAA. [5,6] Since these symptoms are not specific to LMCAA, the clinical diagnosis might be neglected. Thus, other coronary anomalies should be excluded to reach a correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…An anomalous coronary artery origin from the opposite sinus with an intra-mural or an inter-arterial course is well described as a cause of sudden death, 2 but occlusion of the left main coronary artery has not, presumably due to its rarity. 3 Left main coronary artery atresia differs from an intramural or inter-arterial course of an anomalous coronary artery, as the blood flows retrograde from smaller calibre collateral arteries to larger calibre left-sided vessels. 4 Musiani et al hypothesise the collateral vessels are inadequate to meet the myocardial demand which leads to cardiac and coronary insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 A review of literature reveals numerous other case studies with delayed diagnosis of left main coronary artery atresia. [3][4][5][6] Amaral et al described two paediatric cases confirmed via coronary angiography or direct inspection in the operating room, despite normal coronaries on echocardiogram. Shah et al described a paediatric case with recurrent exertional syncopal episodes, an echocardiogram with prominent right coronary artery (otherwise normal), normal exercise testing and diagnosis confirmed by cardiac catheterisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported the incidence of coronary artery anomalies is approximately 0.6%–1.3% in an angiographic series and 0.3% in an autopsy series . Congenital left main coronary atresia (LMCA) is an extremely rare anomaly when the left main coronary ostium ends blindly and the left coronary artery (LCA) is perfused via collateral flow from the right coronary artery (RCA) .…”
Section: Introductionmentioning
confidence: 99%